Propuesta de un manual de funciones, valuación de puestos y reglamento de admisión y empleo para la empresa Mecánica Industrial Ojeda de la ciudad de Loja - Jaramillo Torres, Diana Carolina (2015)
This thesis is titled, "Proposal of a Manual of functions, posts and Valuation Rules of Admission and Employment Business Industrial Mechanical Ojeda city of Loja" This work has as main objective the development since the company since its inception Industrial Mechanical Ojeda, has not a manual of functions, making it difficult for employees to know their duties and responsibilities within the company. Also it lacks a Regulation of Admission and Employment decision instrument in labor and internal affairs, contributing an environment of uncertainty because they have not been established norms of labor behavior they must meet each of the employees and workers of mechanics , this is evidenced by the lack of communication and not responsible for their obligations; these factors contribute to the poor performance of staff working in the company, which increases the service and poor utilization of resources. It currently has 18 employees, the same as most are not well defined functions to be performed and the distribution of its activities, does not have a suitable structure because it does not have clearly defined functions to be developed by each employee in skills base level of professional knowledge, limiting the development and growth of the company. After it raised the proposal for a manual of the same functions consisting of 13 sheets that describe the nature of the position, duties, responsibilities and minimum requirements needed for each job, regulation of admission and employment proposed, the same which describes the phases of a proper recruitment, selection, hiring, induction and training for staff working in mechanics. With regard to the valuation of positions, the basic purpose is to establish the internal values or hierarchies of jobs to determine grades and ranks of payments, thereby thus ensure internal equity in the structure of wages, the method used for the valuation of positions, it has opted for the allocation of points, because it allows a systematic comparison of jobs. This method consists of four factors, degrees and points are then converted into monetary value. For the assessment has taken into account the following factors: education, experience, initiative, responsibility per person per equity and money; stress, physical, mental and working conditions or risks. In Mechanical Ojeda 4 degrees assigned to education, experience 4 to 3 on the initiative, responsibility 4 per person, 4 team responsibilities are assigned, 3 degrees of mental effort, 3 physical effort and finally 2 at risk. With regard to the salary adjustment was conducted by the sum of the salaries received by employees currently divided to the sum of the points according to the job title, the recovery factor obtained was 1.73 this factor was applied to those values that were below the line in the graph, the same representing a salary which does not correspond to the roles and responsibilities that develop in the assigned position, only the manager and the security guard are above the line. Finally, conclusions and recommendations are presented with the most relevant human talent working in the Industrial Mechanics Ojeda, who know the main tasks or duties of the position and the requirements that the position requires, due to the lack of a description and analysis of each since it exists in the company, within the recommendations it suggested Manual Functions and Valuation of posts is considered in order to systematically evaluate the performance of its employees